(untitled) (CIPEEX, 2026)
INTRODUCTION: Aging leads to a decline in organic functions, contributing to frailty, with sarcopenia and muscle strength standing out. Their association results in a condition that compromises postural balance and increases the risk of falls in older adults. OBJECTIVE: To analyze the association between sarcopenia, muscle strength, postural balance, and fall risk in the elderly. METHOD: Cross-sectional study conducted with 59 older adults at the Open University for Older Adults (UniAPI), UniEVANGÉLICA. Postural balance and fall risk were assessed using the Timed Up and Go Test (TUGT). Sarcopenia screening was performed through calf circumference combined with the SARC-F questionnaire, and muscle strength of upper and lower limbs was evaluated using handgrip strength and the sit-to-stand test. Statistical analysis was conducted using SPSS, applying frequency distribution, binary logistic regression, and multiple linear regression, adjusted for age and sex, with a 95% significance level (p < 0.05). RESULTS: The mean age was 73.07 ± 6.96 years, with a predominance of females (84.7%). Regarding falls, 42.4% reported at least one episode in the past year; however, 91.5% did not use assistive devices. Sarcopenia was significantly associated with both fall risk and number of falls (p = 0.027 and p = 0.010, respectively), as well as poorer TUGT performance (p = 0.006). Age had a negative impact (p = 0.017), while sex showed no influence on outcomes (p = 0.420). CONCLUSIONS: Sarcopenia, in relation to muscle strength, was the main factor associated with fall risk, fall frequency, and poorer functional performance in the TUGT among the evaluated older adults.